The Contestation Of Religion And Science In The Perspective Of Conspiracy Theory: The Though Of Karl Popper And Ibn Rushd - Muhammad Fadhlurrahman Zakaria; Halid Halid (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
This study explores the intersection between religion and science through the lens of conspiracy theory, specifically by examining the thoughts of Karl Popper and Ibn Rushd. Employing a qualitative method through literature review and philosophical-historical analysis, the research delves into the epistemological frameworks of both thinkers. The findings reveal that Karl Popper criticizes conspiracy theories as pseudoscience lacking falsifiability, while Ibn Rushd promotes the reconciliation of reason and revelation as a path to harmonize science and religion. This article identifies that external factors—such as political interests, cultural narratives, and media influence—often catalyze the conflict rather than inherent contradictions between religion and science. The novelty of this research lies in its interdisciplinary approach combining Western and Islamic philosophical perspectives to address contemporary sociocultural challenges. The study suggests that rational education and philosophical dialogue should be prioritized in shaping policies that aim to reduce societal polarization and promote constructive engagement between religious and scientific communities.